Functional Features of Modern Cardiological Patients (Indian Journal of Public Health Research & Development, 2020)
Context: Modern studies have shown that one of the risk factors for recurrent thrombosis, coronary heartdisease and cerebrovascular pathology is the level of homocysteine in the blood. An analysis was madeof the severity of homocysteinemia in patients with coronary heart disease with episodes of painlessmyocardial ischemia, and it was corrected with B vitamins. 84 patients with coronary heart disease withfunctional angina pectoris I-III were examined. It was found that the combination of hyperhomocysteinemiaand frequent episodes of painless myocardial ischemia is recorded mainly in patients with a high functionalclass of angina pectoris. Reception of B vitamins can significantly reduce the concentration of homocysteinein blood plasma and the frequency of episodes of painless myocardial ischemia.
Keywords: Hyperhomocysteinemia, coronary heart disease, angina pectoris, painless ischemia.